The Application of Nanofiltration Membrane for Palm Oil Mill Effluent Treatment by Adding Polyaluminium Chloride (PAC) as Coagulant - Pinem, Jhon Armedi; Tumanggor, Imanuel; Saputra, Edy (Jurnal Rekayasa Kimia & Lingkungan, 2020)
The rapid development of Crude Palm Oil (CPO) production has led to an increase in the production of Palm Oil Mill Effluent (POME) as well. POME will cause problems in the environment because contains high contaminants. This study aims to investigate the effect of the coagulant Polyaluminium Chloride (PAC) variations and the membranes operating pressure on the POME treatment process using the nanofiltration membrane (NF) with the coagulation-flocculation process as pre-treatment. The PAC was used in the coagulation-flocculation process with variations in concentration (5.0; 5.5; 6.0; 6.5; 7.0 g/L). The process was completed by a rapid stirring of 200 rpm for 5 minutes, followed with slow stirring at 60 rpm for 15 minutes and settling time for 30 minutes. The process of membrane nanofiltration was carried out for 60 minutes with variations in operating pressure (8.0; 9.0; and 10 bars). In each treatment process, effluent quality testing was carried out with Biochemical Oxygen Demand (BOD5), Chemical Oxygen Demand (COD), Total Suspended Solid (TSS) and oil/fat as parameters. In addition, an analysis of permeate fluxes and rejection of NF membrane was also carried out. The results of the analysis suggested that the best coagulant doses are 6.0 g/L with the reduction percentage of BOD, COD, TSS and oil/fat at 78.85%; 68.57%; 92.77% and 92.31% respectively. The highest percentage of NF membrane rejection was found at a pressure of 10 bar, which is equal to 94.71%; 94.86%; 97.92% and 95% respectively for BOD, COD, TSS and oil/fat with a flux value of 7.16 L/m2.hours.